Study on optimization of cryopreserved bovine spermatozoa using magnetic activated cell sorting system on viability, motility and HSP70 gene expression / Syarifah Faezah Syed Mohamad - Syed Mohamad, Syarifah Faezah (2013)
Cryopreservation is a technique commonly used to preserve cells for long time storage. It is widely used in livestock industry to store male gametes in liquid nitrogen. In this study, three Bos taurus adult were used. Semen collected from these bulls were grouped into two; 1) treatment group which was subjected to Magnetic Activated Cell Sorting System (MACS) then cryopreserved, and 2) the untreated group which was directly cryopreserved without MACS. Prior to cryopreservation, sperm were incubated in Annexin V then placed in the column attached to the magnetic stand. Semen analysis was done by using the Computer Assisted Sperm Analysis software (CASA). Parameters included were sperm velocity (VAP, VCL, VSL; nm/s) and sperm progression (WOB, LIN, STR; %). Sperm viability was determined by using eosin-nigrosin staining technique. Effects of different thawing temperatures and times were analysed by using iQ™SYBR® Green assay for qPCR with GAPDH as the reference gene. Cryo-capacitation like damage was then identified using chlorotetracycline/Hoechst staining assay under blue-violet illumination of fluorescent microscope (excitation: 400-440 nm, emission: 470 nm). All statistical data were analysed using SPSS version 14; p-value was set at 0.05 as significant level. Findings revealed that thawing at 37°C for 30 seconds for MACS processed sample was most suitable compared to other thawing procedures. At 37°C for 30 seconds, it produced significant data of VCL nm/s, 133.31 [im/s ± 4.38 (p = 0.004), RNA concentration of 83.84 ng/ pi (p = 0.001), relative gene expression of HSP70, 0.097 ± 0.027 (p = 0.048) and CTC/Hoechst assay, 50.6% of F pattern (p = 0.045). Hence, we can speculate that the usage of MACS as the sperm preparation technique as able to enhance sperm cryosurvival rate after cryopreservation, however the fertilization potential of these sperm has yet to be determined.